2023
DOI: 10.15252/embj.2022112165
|View full text |Cite
|
Sign up to set email alerts
|

Two antagonistic response regulators control Pseudomonas aeruginosa polarization during mechanotaxis

Abstract: The opportunistic pathogen Pseudomonas aeruginosa adapts to solid surfaces to enhance virulence and infect its host. Type IV pili (T4P), long and thin filaments that power surface‐specific twitching motility, allow single cells to sense surfaces and control their direction of movement. T4P distribution is polarized to the sensing pole by the chemotaxis‐like Chp system via a local positive feedback loop. However, how the initial spatially resolved mechanical signal is translated into T4P polarity is incompletel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(31 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…We have previously reported that pilHLOF and pilHGOF mimic the inactive (non-phosphorylated) and active (phosphorylated) state of PilH, respectively, as assessed by twitching motility, cAMP production, and localization assays 34 . We observed that pilHLOF phenocopied DpilH with increased ChpB asymmetric polar localization, while ChpB-mNG localization was comparable to WT in ensure that upon twitching reversals, PilJ at the new leading pole is methylated and "poised" to efficiently promote Pil-Chp signaling once mechanosensing occurs (Figure 7).…”
Section: Pilj Methylation Increases In Response To Mechanosensing And...mentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that pilHLOF and pilHGOF mimic the inactive (non-phosphorylated) and active (phosphorylated) state of PilH, respectively, as assessed by twitching motility, cAMP production, and localization assays 34 . We observed that pilHLOF phenocopied DpilH with increased ChpB asymmetric polar localization, while ChpB-mNG localization was comparable to WT in ensure that upon twitching reversals, PilJ at the new leading pole is methylated and "poised" to efficiently promote Pil-Chp signaling once mechanosensing occurs (Figure 7).…”
Section: Pilj Methylation Increases In Response To Mechanosensing And...mentioning
confidence: 99%
“…Nevan Krogan has a financially compensated consulting agreement with Maze Therapeutics. He is the President and is on the Board of Directors of Rezo The mechanical signals, sensed by PilJ, initiate a positive feedback loop that continuously activates the Pil-Chp system at the leading pole 33,34 . The lagging pole has fewer or no TFP and thus less activation of the Pil-Chp system.…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Yarrington, Limoli and colleagues shows that the PilJ likely detects phenyl soluble modulins via its periplasmic domain as a ligand to trigger signaling, a finding that strongly suggests that PilJ can function like a classic MCP (25). Others have recently uncovered the function of PilG and PilH in twitching motility and surface adaptation (26,27). In contrast, how surface engagement by T4P triggers cAMP signaling in a PilJ-dependent manner is still an open question.…”
Section: Introductionmentioning
confidence: 99%
“…Other three receptors McpB/Aer2, WspA, and PilJ are involved in an F7-type pathway of unknown function, an alternative cellular function pathway that mediates c-di-GMP synthesis, and type IV pili chemosensory pathway that is associated with twitching motility, respectively. The latter two pathways were found to perform mechano-and surface sensing rather than chemosensing (29)(30)(31). Of the 18 chemoreceptors with a periplasmic LBD that belong to the F6 pathway (28), ten have been functionality annotated (Table 1).…”
Section: Introductionmentioning
confidence: 99%